Scientific connotation of the compatibility of traditional Chinese medicine from the perspective of the intestinal flora - Yuan Gao; Xiaoxia Wu; Ning Zhao; Ning Zhao; Dong Bai (Frontiers Media S.A., 2023)
Revealing the connotation of the compatibility of Chinese medicines (CM) is a requirement for the modernization of traditional Chinese medicine (TCM). However, no consensus exists on the specific mechanism of traditional Chinese medicine compatibility (TCMC). Many studies have shown that the occurrence and development of diseases and the efficacy of CM are closely related to intestinal flora (IF), which may provide a new perspective to understand the theory of TCM. This study aimed to summarize the relationship between the changes in IF before and after the compatibility of different drugs and the synergistic, toxicity reduction, and incompatibility effects of drug pairs from the perspective of the effects of CM on the IF and the regulation of microbial metabolites. These studies showed that the effect of drug pairs on the composition of the IF is not a simple superposition of two single drugs, and that the drug pairs also play a specific role in regulating the production of intestinal bacterial metabolites; therefore, it has a different pharmacodynamic effect, which may provide a perspective to clarify the compatibility mechanism. However, research on the interpretation of the scientific connotations of TCMC from the perspective of the IF is still in its infancy and has limitations. Therefore, this study aimed to summarize previous research experience and proposed to conduct a deep and systematic study from the perspective of drug pair dismantling, IF, intestinal bacteria metabolite, organism, and disease to provide a reference for scientific research on the compatibility mechanism of CM.